Asymmetry in Gasoline Price Transmission: How do Fuel Pricing Strategy and the Ethanol Addition Mandate Affect Consumers? - Raeder, Francisco Teixeira; Rodrigues, Niagara; Losekann, Luciano Dias (International Journal of Energy Economics and Policy, 2022)
This work aims at verifying the existence of asymmetries in gasoline price transmission between refining, distribution, and gas stations. The analysis covers two moments: before (2006-2016) and after (2016-2020) the new fuel pricing strategy adopted in the refining sector. Before 2016, gasoline prices in refineries were stable due to price intervention. After that, prices fluctuated in convergence with the international market. In this paper, we also consider ethanol prices. Due to an addition mandate, ethanol prices influence gasoline price’ dynamics. Our hypothesis is that there are “rocket” and “feather” patterns. This means that positive changes in costs are rapidly and fully transmitted to prices, while negative cost changes tend to be transmitted gradually. As a consequence, there is a cost for consumers. We use Dynamic Ordinary Least Squares estimators and Error Correction Models to test the presence of asymmetries and Cumulative Response Functions to measure consumer cost. Results confirm an asymmetric price transmission and indicate that the new pricing strategy has changed the readjustment dynamic. Although we detect asymmetries in both periods, the new pricing strategy proved to be better for consumers, as social costs decreased after its adoption.